Hierarki Pengaruh Organisasional dalam Pemberitaan Calon Presiden-Wakil Presiden Pemilihan Umum 2024 : Studi Kasus pada Media Online Sindonews.com - Syalahuddin Al-Ayubi Ramadhani; Makroen Sanjaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
As the 2024 presidential election approaches, mass media widely disseminate information about presidential and vice-presidential candidates. The registration period, from October 19 to 25, 2023, became a major political event that attracted extensive media attention. Ideally, media outlets should report political events independently, without external influence. However, Sindonews.com shows signs of organizational influence in its coverage of the candidate registration process. This study examines the factors shaping news coverage using the Media Content Hierarchy Theory by Shoemaker & Reese (1996), which identifies five levels of influence: individual, media routines, organizational, extramedia, and ideological. Through a qualitative case study method, employing in-depth interviews, documentation, and observation, the findings reveal that organizational influence is the dominant factor affecting Sindonews.com's reporting. This is largely due to its affiliation with Harry Tanoesoedibjo, who owns Sindonews.com and leads Partai Perindo, a party that supported Ganjar Pranowo and Mahfud MD in the 2024 election. Consequently, the media coverage reflected this political alignment, underscoring how ownership and political affiliations impact journalistic objectivity in Indonesia’s digital news landscape.